PERTUMBUHAN DAN PERKEMBANGAN BENIH TUMBUHAN GROWTH AND CEVELOPMENT OF PLANT SEEDS - Pilza Ummi; Dea Octa Anggriani (JOURNAL SAINS STUDENT RESEARCH, 2025)
Indonesia has many different types of plants. The climate and soil help these plants thrive and thrive. Therefore, we should be grateful for this gift from God. All living things grow and change. As living things go through their lives, they grow and change, and these two things occur simultaneously. Growth and development are not the same thing. This study aims to determine the importance of light for mung bean growth. This research used qualitative methods. The participants were fifth-grade students from SD Negeri 050750 Pangkalan Brandan in Langkat Regency. The results showed that light significantly affects the growth of mung bean sprouts. Sprouts grown under bright light were healthier than sprouts grown without light.